Freequency of Depression in Care Givers of Drug Addict - Shanza Nazir, Amjad Hussain Balouch, Muhammad Ayub, Ratan Kumar, Arjan Kumar, Sangeet (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Drug abuse is a substance-related disorder in which a person uses a substance in quantities or ways that are hazardous to them or others. It has been known for some time that humans are susceptible to addiction. Symptoms of depression are particularly common in relatives of drug addicts. So we conducted this study to find the evidence in these case to know the extent of depression in relatives of drug abusers. Objective: To determine the frequency of depression in relatives of drug abusers presenting in outpatients department Material & Methods Study Design: It was cross sectional study Setting: Department of Psychiatry, Jinnah Hospital, Lahore Duration: 6 months after approval of synopsis i.e. from: 29-05-2017 to 29-11-2017 Data collection: After meeting the inclusion criteria 100 patients were enrolled. Then patients assessed by using HADS scoring system by researcher herself. If HADS score ≥11, then depression labeled. Results: The mean age of the patients was 41.33±13.99 years. There were 29 males and 71 female caregivers. About 24(24%) patients were illiterate. In this study the mean HADS score was 7.81±5.86. The depression in relatives of drug abusers was found in 26(26%) patients. Conclusion: According to this study the frequency of depression in relatives of drug abusers presenting in outpatients department is 26%.